DESIGNING RO-LEX APPLICATION FOR DYSLEXIC STUDENTS - Iin Baroroh Ma'arif; Rizki Amalia Amalia; Winda Rochma Rochma (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
This research aims at designing learning media named RO-LEX for Dyslexic Students and ease the students in learning English. It focuses only on reading skill. The research method used is Research and Development (RD) using Borg and Gall model that consists of ten procedures, they are: 1) Research and Information Collecting, 2) Planning, 3) Develop Preliminary Form of Product, 4) Preliminary Field Testing, 5) Main Product Revision, 6) Main Field Testing, 7) Operational Product Revision, 8) Operational Field Testing, 9) Final Product Revision, and 10) Dissemination and Implementation. From the processes conducted, the researcher got the results of the research. 1) The result of material validation is 80 (very good category), 2) The result of media validation is 69 (good category), 3) The result of dyslexic expert was 59 (good category). Based on the results, the researcher concluded that this RO-LEX application is deserved to be used for dyslexic students as an English learning media.